Hashim bin Utba: His Biography and Role in Islam - Jabbar Shibib, Bashar Abdul- (Opción, 2019)
The aim of the study is to investigate biography of Hashim bin Utba and his role in Islam via qualitative comparative methods. As a result, our Arab Islamic history has witnessed many influential figures in historical events, especially the character of Hashim bin Utba, who was characterized by determination, courage. Although he was mentioned many of our historical sources about his positions and wars, he overlooked the year of his birth and some of his wives and children. In conclusion, he was known of his strength, tolerance, bravery, morals, and locality in protecting Islam from enemies